Characterization and optimization of cathodic conditions for H2O2 synthesis in microbial electrochemical cells. (November 2015) - Sim, Junyoung; An, Junyeong; Elbeshbishy, Elsayed; Ryu, Hodon; Lee, Hyung-Sool
Highlights: H2 O2 conversion efficiency increased by 65% using O2 diffusion. The maximum H2 O2 production rate was 141 mg H2 O2 /L-h. O2 diffusion to the cathode would be rate-limiting for H2 O2 production. Abstract: Cathode potential and O2 supply methods were investigated to improve H2 O2 synthesis in an electrochemical cell, and optimal cathode conditions were applied for microbial electrochemical cells (MECs). Using aqueous O2 for the cathode significantly improved current density, but H2 O2 conversion efficiency was negligible at 0.3–12%. Current density decreased for passive O2 diffusion to the cathode, but H2 O2 conversion efficiency increased by 65%. An MEC equipped with a gas diffusion cathode was operated with acetate medium and domestic wastewater, which presented relatively high H2 O2 conversion efficiency from 36% to 47%, although cathode overpotential was fluctuated. Due to different current densities, the maximum H2 O2 production rate was 141 mg H2 O2 /L-h in the MEC fed with acetate medium, but it became low at 6 mg H2 O2 /L-h in the MEC fed with the wastewater. Our study clearly indicates that improving anodic current density and mitigating membrane fouling would be key parameters for large-scale H2 O2 -MECs.